The feminist avant-garde in American poetry - Frost, Elisabeth A. (Elisabeth Ann), 1963- (University of Iowa Press, 2003)
The Feminist Avant-Garde in American Poetry offers a historical and theoretical account of avant-garde women poets in America from the 1910s through the 1990s and asserts an alternative tradition to the predominantly male-dominated avant-garde movements. Elisabeth Frost argues that this alternative lineage distinguishes itself by its feminism and its ambivalence toward existing avant-garde projects; she also thoroughly explores feminist avant-garde poets' debts and contributions to their male counterparts. -- Publisher website 20241216
Keywords: American poetry -- 20th century -- History and criticism.; Feminism and literature -- United States -- History -- 20th century.; Avant-garde (Aesthetics) -- United States -- History -- 20th century.; Women and literature -- United States -- History -- 20th century.; American poetry -- Women authors -- History and criticism.; Experimental poetry, American -- History and criticism.; Feminist poetry, American -- History and criticism.; Poésie américaine -- 20e siècle -- Histoire et critique.; Femmes et littérature -- États-Unis -- Histoire -- 20e siècle.; Poésie expérimentale américaine -- Histoire et critique.; Poésie féministe américaine -- Histoire et critique.; LITERARY CRITICISM -- Poetry.; SOCIAL SCIENCE -- Women's Studies.; American poetry; American poetry -- Women authors; Avant-garde (Aesthetics); Experimental poetry, American; Feminism and literature; Feminist poetry, American; Women and literature; United States; Frauenlyrik; Feminismus; Avantgarde; USA; 1900-1999; Geschichte 1910-2000.; Electronic books; Criticism, interpretation, etc.; History